Factorise

Asked by Shank10 | 18th Aug, 2008, 12:00: PM

Expert Answer:

 (a)  put  x = --1  then   x3 --12x+ 47 x +60  will become ( --1)--12( --1)2   +  47 ( --1) +60  =  --1 --12 --47 + 60  =0

 therefore  x + 1  is  a factor

 

 (b)  put  x == --2  then   6x3   + 11 x 2 - 4x - 4 will  become   6 ( --2)3  + 11 ( - 2)2 --4 (--2)  -4 = --48 + 44 +8 --4= 52 --52 ==0  .. therefore   x + 2  is a factor

Answered by  | 18th Aug, 2008, 01:33: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.